PERAN PERSEPSI SWITCHING COST MEMODERASI CUSTOMER SATISFACTION TERHADAP CUSTOMER LOYALTY STUDI PELANGGAN PT BANK MANDIRI (PERSERO), Tbk. - Juana, I Made Predanggapati; Sukaatmadja, I Putu Gde; Yasa, Ni Nyoman Kerti (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.06.NO.02.TAHUN 2017, 2017)
This study aims to determine the role of switching cost moderation in the relationship between customer satisfaction to customer loyalty in the customer's working capital loan PT Bank Mandiri (Persero), Tbk.Population in this research is the customer of working capital loans by collecting data through a survey of the users of credit for working capital and sampling technique used in this study is a Proportionate Stratified Random Sampling of 200 samples. Hypothesis testing using simple linear regression analysis techniques and moderated regrated analysis (MRA).The results showed that: (1) Customer satisfaction is not significant on customer loyalty. (2) Switching Cost able to moderate a positive and significant influence on customer loyalty customer satisfaction while decreasing customer satisfaction though.Suggested to further research to investigate other variables that affect customer loyalty and for companies to pay attention to the switching cost variable as strategy extra such us to increase a penalty fee, increase a relationship between customers, and create a point rewards program as a way to retain customers so that customers will feel the loss of benefits / relationship if they switch to another competitors.
Keywords: Banking Services, Working Capital Loans, Switching Cost